Evaluate, without using a calculator, the exact value of .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
We use the identity t a n 2 x + 1 = s e c 2 x , or, t a n 2 x = s e c 2 x − 1 = c o s 2 x 1 − 1 .
It is a (not-so-well-known) fact that c o s 3 6 ∘ = 4 5 + 1 . It is another fact that c o s 7 2 ∘ = 4 5 − 1
So, our equation becomes
t a n 2 3 6 ∘ + t a n 2 7 2 ∘ = c o s 2 3 6 ∘ 1 − 1 + c o s 2 7 2 ∘ 1 − 1 = ( 5 − 1 4 ) 2 + ( 5 + 1 4 ) 2 − 2 .
Rationalizing the denominator and expanding, we get that the expression is equal to 1 0 .